Pengaruh ukuran kantor akuntan publik, komite audit, profitabilitas dan leverage terhadap manajemen laba pada perusahaan manufaktur yang terdaftar di bursa efek indonesia periode 2017-2020 - Kaur, Rimel Jit; Wan Afri Luter Halawa; Hutahaean, Thomas Firdaus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Manufacturing companies reduce purchasing and inventory activities to control spending. This decrease in profit has resulted in manufacturing in general reducing costs, decreasing demand and decreasing production capacity due to public purchasing power that has not improved and has an impact on market demand. on the Indonesia Stock Exchange for the 2017-2020 period. The quantitative approach processes the data. Types of quantitative research and the nature of causal relationships. The population is 177 Manufacturing Companies Listed on the IDX in 2017-2020. The sample is 43 companies. The method of data analysis is multiple linear regression test. The result of the research is that the size of the public accounting firm has no effect on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The Audit Committee, Profitability and Leverage have an effect on Earning Management in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The size of the Public Accounting Firm, Audit Committee, Profitability and Leverage has an effect on Earnings Management in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2020 period.